Language Control in Bilinguals: Monitoring and Response Selection. (1st April 2015) - Branzi, Francesca M.; Della Rosa, Pasquale A.; Canini, Matteo; Costa, Albert; Abutalebi, Jubin
Abstract : Language control refers to the cognitive mechanism that allows bilinguals to correctly speak in one language avoiding interference from the nontarget language. Bilinguals achieve this feat by engaging brain areas closely related to cognitive control. However, 2 questions still await resolution: whether this network is differently engaged when controlling nonlinguistic representations, and whether this network is differently engaged when control is exerted upon a restricted set of lexical representations that were previously used (i.e., local control) as opposed to control of the entire language system (i.e., global control). In the present event-related functional magnetic resonance imaging study, we investigated these 2 questions by employing linguistic and nonlinguistic blocked switching tasks in the same bilingual participants. We first report that the left prefrontal cortex is driven similarly for control of linguistic and nonlinguistic representations, suggesting its domain-general role in the implementation of response selection. Second, we propose that language control in bilinguals is hierarchically organized with the dorsal anterior cingulate cortex/presupplementary motor area acting as the supervisory attentional system, recruited for increased monitoring demands such as local control in the second language. On the other hand, prefrontal, inferior parietal areas and the caudate would act as the response selection system, tailored for language selection for both local and global control.